Optimizing control strategies for urine nitrification: narrow pH control band enhances process stability and reduces nitrous oxide emissions - Faust, Valentin; Boon, Nico; Ganigué, Ramon; Vlaeminck, Siegfried E.; Udert, Kai M. (Frontiers in Environmental Science, 2023)
Nitrification is well-suited for urine stabilization. No base dosage is required if the pH is controlled within an appropriate operating range by urine feeding, producing an ammoniumnitrate fertilizer. However, the process is highly dependent on the selected pH set-points and is susceptible to process failures such as nitrite accumulation or the growth of acid-tolerant ammonia-oxidizing bacteria. To address the need for a robust and reliable process in decentralized applications, two different strategies were tested: operating a two-position pH controller (inflow on/off) with a narrow pH control band at 6.20/6.25 (∆pH = 0.05, narrow-pH) vs a wider pH control band at 6.00/6.50 (∆pH = 0.50, wide-pH). These variations in pH also cause variations in the chemical speciation of ammonia and nitrite and, as shown, the microbial production of nitrite. It was hypothesized that the higher fluctuations would result in greater microbial diversity and, thus, a more robust process. The diversity of nitrifiers was higher in the wide-pH reactor, while the diversity of the entire microbiome was similar in both systems.However, the wide-pH reactor was more susceptible to tested process disturbances caused by increasing pH or temperature, decreasing dissolved oxygen, or an influent stop. In addition, with an emission factor of 0.47%, the nitrous oxide (N2O) emissions from the wide-pH reactor were twice as high as the N2O emissions from the narrow-pH reactor, most likely due to the nitrite fluctuations. Based on these results, a narrow control band is recommended for pH control in urine nitrification.